Model Pendampingan Instruksional bagi ABK di SD Negeri Tingkir Tengah 02 Salatiga - Hema Pelangi Sawitri Ariom; Erika Salsabella Aurelia; Sriyanto Sriyanto (AUDIENSI: Jurnal Pendidikan dan Perkembangan Anak, 2025)
This study aims to describe the instructional support model for Children with Special Needs (CSN) at SDN Tingkir Tengah 02 Salatiga. The study employed a descriptive qualitative approach, with primary data obtained from interviews with classroom teachers, special education teachers, and school personnel involved in the implementation of inclusive education. Data were collected through interviews, observations, and documentation. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the instructional support model is implemented through student needs assessments, the development of Individualized Education Programs (IEPs), differentiated instruction, the use of adapted learning media, and individualized approaches based on each student's characteristics. The support process is carried out through collaboration among classroom teachers, special education teachers, school principals, and parents to promote students' academic, social, and emotional development. Supporting factors in the implementation of instructional support include the school's commitment, collaboration among educators, and family support. However, several challenges were identified, including limited facilities and infrastructure, an insufficient number of support personnel, and the need to enhance teachers' competencies in addressing diverse student needs. Overall, the instructional support model implemented at the school has been effective in supporting the learning success of children with special needs within an inclusive education setting.